Islamic Value-Based Health Service Model Satisfaction and Behavior Complaint Patients in Hospital: SEM-PLS Approach - Susi Handayani; Endah Saptutyningsih; Diah Setyawati Dewanti (UNIVED Press, 2026)
This study aims to analyze the influence of an Islamic value-based healthcare service model on patient satisfaction and its implications for patient complaint behavior at PKU Muhammadiyah Mayong Hospital, Jepara. Using a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method, data were collected from respondents through a structured questionnaire. The construct of the Islamic value-based healthcare service model integrates the prophetic values of shiddiq, amanah, fathanah, tabligh, and ihsan as service indicators. The results show that the implementation of Islamic values contributes positively and significantly to improving patient satisfaction holistically. Furthermore, the Islamic value-based healthcare service model has been proven effective in reducing the tendency of patient complaint behavior, both directly and through the mediation of patient satisfaction. Managerially, strengthening spiritual values is not merely an ethical aspect, but a strategic instrument to mitigate the risk of service failure and build patient trust as an economic asset of the hospital. Synchronizing medical professionalism and Islamic spirituality is the key to sustainable competitive advantage for faith-based healthcare institutions.